Effect of traffic density on heavy metal content of soils and vegetation cover along roadsides, case study: City of Hamedan - Bahareh Lorestani; Mehrdad Cheraghi; Sobhan Ardakani Soheil (Muhandisī-i Bihdāsht-i Muḥīṭ, 2023)
Background & Objective: Nowadays, trace elements are known as useful indicators for monitoring of environmental pollution caused from traffic emmissions. Therefore, this study was conducted to assess the effect of urban traffic and distance from the street side on heavy metals (Pb, Cd and Cu) concentration in surface soil and plant species of roadsides environment of city of Hamedan, west of Iran. Methods: In this descriptive study, a total of 48 surface soil and plant samples were collected from four areas of city of Hamedan with different traffic density. After samples preparation, the concentrations of the analyzed elements in the soil and plant samples were determined using ICP-OES. Also, all statistical analyses of the obtained data were performed using SPSS software version 19.0. Results: Based on the results obtained, metals accumulation in soils and plants of the area with heavy traffic volume especially Basij Boulevard were higher than the other sampling areas. Also, distance from street side had been inverse relation with metals accumulation in soil and plant samples. So as the most accumulation of elements was recorded for samples collected at a distance of 5.0 m from street side. Conclusion: Generally, inverse relation of metals accumulation in soil and plant samples with distance from street side might be related to vehicular emissions. Moreover, the results of this study also could be useful for managers and planners in the fields of architecture and urban design, urban land use planning, and urban traffic control managers.